2007
DOI: 10.1177/154405910708600115
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Preserves Dentin Bond in vitro

Abstract: Loss of hybrid layer integrity compromises resin-dentin bond stability. Matrix metalloproteinases (MMPs) may be partially responsible for hybrid layer degradation. Since chlorhexidine inhibits MMPs, we hypothesized that chlorhexidine would decelerate the loss of resin-dentin bonds. Class I preparations in extracted third molars were sectioned into two halves. One half was customarily restored (etch-and-rinse adhesive/resin composite), and the other was treated with 2% chlorhexidine after being acid-etched befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
348
2
89

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(458 citation statements)
references
References 20 publications
19
348
2
89
Order By: Relevance
“…Previous studies (13,24) have shown that caries-affected dentin applying the 2% CHX after acid etching, in order to minimize the degradation of resin-dentin bonds, does not negatively influence the immediate bond strength to sound permanent dentin. Similar results were observed in the present study in primary teeth, corroborating the findings of Ricci et al (17).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies (13,24) have shown that caries-affected dentin applying the 2% CHX after acid etching, in order to minimize the degradation of resin-dentin bonds, does not negatively influence the immediate bond strength to sound permanent dentin. Similar results were observed in the present study in primary teeth, corroborating the findings of Ricci et al (17).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the adequate immediate bond strength, in vivo (12) and in vitro (13) studies have revealed that resindentin bonds deteriorate over time. It has been speculated that a decreasing concentration gradient of resin monomer diffusion within the acid-etched dentin, and a subsequent resin elution from hydrolytically unstable polymeric hydrogels within the hybrid layers (14) leave the exposed collagen fibrils susceptible to hydrolytic and enzymatic degradation, mediated by endogenous metalloproteinases (MMPs) (15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that matrix metalloproteinase (MMP) inhibitors, such as chlorhexidine (CHX) and more recently sodium fluoride (NaF), are able to preserve the structural integrity of the hybrid layer and consequently improve the longevity of restorations (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%